2016
DOI: 10.3390/mi7050078
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a 3D Cellular Computer Using Folded E-Blocks

Abstract: The assembly of integrated circuits in three dimensions (3D) provides a possible solution to address the ever-increasing demands of modern day electronic devices. It has been suggested that by using the third dimension, devices with high density, defect tolerance, short interconnects and small overall form factors could be created. However, apart from pseudo 3D architecture, such as monolithic integration, die, or wafer stacking, the creation of paradigms to integrate electronic low-complexity cellular buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Also, solidification of liquid hinges composed of solder or polymers on cooling allow such self‐folded polyhedra to be permanently bonded and sealed in‐place. Consequently, such polyhedra could be used as building blocks for aggregative assembly of 3D metamaterials (Figure b), 3D electrical networks, (Figure c) and 3D computational devices, which is not presently possible by other approaches. Also, as previously mentioned, it would be interesting to manipulate surface properties or surface tension to create dynamic and reversible structures.…”
Section: Resultsmentioning
confidence: 99%
“…Also, solidification of liquid hinges composed of solder or polymers on cooling allow such self‐folded polyhedra to be permanently bonded and sealed in‐place. Consequently, such polyhedra could be used as building blocks for aggregative assembly of 3D metamaterials (Figure b), 3D electrical networks, (Figure c) and 3D computational devices, which is not presently possible by other approaches. Also, as previously mentioned, it would be interesting to manipulate surface properties or surface tension to create dynamic and reversible structures.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the spherical geometry allows the acceptance of light from all spatial directions. Figure a (iii) shows a polyhedral electronic block integrated with a variety of electronic modules, such as transistors and chips . Simulation results showed that the compactness of 3D architectures is 63.2% better than the 2D layouts.…”
Section: Folding Assembly Methods and Applicationsmentioning
confidence: 99%
“…(iii) The required cell number of 3D integrated gates in comparison with the 2D layout at the same performance level. Adapted under the terms of the CC‐BY 4.0 Creative Commons Attribution License . Copyright 2016, The Authors, published by MDPI.…”
Section: Folding Assembly Methods and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such devices enable wide-angle steering of optical beams and simplify engineering embodiments, providing advanced building blocks for light detection and ranging (LIDAR), spectroscopy, and other technologies. Other electronic or optical devices, including tunable inductors and antennas, optical metamaterials, and 3D wiring of electronic components, are also achievable though origami and kirigami routes.…”
Section: Fundamental Explorations Of Oknsmentioning
confidence: 99%